Microvesicle release and micellar attack as the alternative mechanisms involved in the red-blood-cell-membrane solubilization induced by arginine-based surfactants - Fait, María Elisa (2017)
Two novel arginine-based surfactants, Bz-Arg-NHC10 and Bz-Arg-NHC12, were characterized with respect to surface properties and their interaction with human red-blood-cell (HRBC) membranes. The values for critical micellar concentration (CMC), the maximum surfactant adsorption at the air-liquid interface, and the area per molecule indicated better surface properties for Bz-Arg-NHC12. The observation of cylindrical worm-like aggregates of Bz-Arg-NHCnvia atomic-force microscopy supported the predictions based on the value of the surfactant-packing parameter (SPP). Erythrocyte-membrane solubilization was effected by surfactant aggregates since cell lysis became evident at only surfactant concentrations above the CMC. Changes in HRBC shape observed at different surfactant concentrations led to the conclusion that a slow mechanism based on the insertion of surfactant monomers into the HRBC membrane, followed by a shedding of microvesicles was responsible for the hemolysis produced by both surfactants at the lower concentrations tested. In contrast, the extraction of membrane lipids upon collisions between HRBCs and surfactant aggregates competes with and prevents microvesicle release at the higher concentrations assayed.